How to manufacture assemblies using tungsten inert gas (TIG) welding
A pre-coated steel substrate with a flux of titanate and nanoparticles enhances TIG welding penetration and mechanical properties, addressing the inefficiencies of traditional methods by stabilizing the arc and improving weld quality.
Patent Information
- Application Number
- JP2021561678
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-17
- Filing Date
- 2020-04-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-04-16
AI Technical Summary
Existing TIG welding methods face challenges in achieving deep weld penetration and optimal mechanical properties in steel substrates, necessitating multiple passes that reduce productivity.
A pre-coated steel substrate using a flux comprising titanate and nanoparticles, such as TiO2 and SiO2, with specific size and proportion, applied through methods like spin coating, to enhance weld penetration by modifying the weld pool's physical properties and stabilizing the arc.
The flux improves weld penetration and mechanical properties by increasing the depth-to-width ratio and reducing part distortion, while maintaining arc stability and weld quality.
Smart Images

Figure 0007603610000001 
Figure 0007603610000002 
Figure 0007603610000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pre-coated steel substrate, the coating of which comprises at least one titanate and at least one nanoparticle, a method for producing the assembly, a method for producing the coated metal substrate, and finally the coated metal substrate, which is particularly well suited for the construction and automotive industries. [Background technology]
[0002] It is known to use steel components to manufacture vehicles. Typically, the steel components can be manufactured with high-strength steel plates to achieve a lighter weight for the vehicle body and improve crash safety. The manufacturing of the steel components generally follows welding the steel component with another metal substrate. The welding of two metal substrates can be difficult to achieve due to the lack of deep weld penetration in the steel substrate. This requires several welding passes to be made, reducing productivity.
[0003] Steel parts may be welded by gas tungsten arc welding (GTAW), also known as tungsten inert gas (TIG) welding. TIG is an arc welding process that uses a non-consumable tungsten electrode to form the weld. The weld area and electrode are protected from oxidation or other atmospheric contamination by an inert shielding gas (argon or helium), and a filler metal is usually used, although some welds, known as autogenous welds, do not require one. A constant current welding power source produces electrical energy, which is conducted across the arc through a column of highly ionized gas and metal vapor known as a plasma.
[0004] Patent application WO00 / 16940 discloses that deep penetration gas tungsten arc welding is 2 Ti 3 O 7 Or K 2 TiO 3The authors disclose that this can be accomplished using titanates such as TiO, TiO, etc. The titanates are applied to the weld zone in a carrier fluid paste or as part of the wire filler to produce deep penetration welds in carbon steels, chromium-molybdenum steels and stainless steels, as well as nickel-base alloys. They also use TiO, TiO to control arc wander, bead consistency, and slag and surface appearance of the weld. 2 , Cr 2 O 3 and Fe 2 O 3 Various additional components may be optionally added to the titanate flux, including transition metal oxides such as titanium dioxide, manganese silicide, fluorides and chlorides. 2 O 3 and Cr 2 O 3 It is disclosed that this flux provides weld penetration in carbon steels and nickel-base alloys, but with some hot variation.
[0005] This patent application discloses that the titanate compounds are typically used in the form of high purity powders of about 325 mesh or finer, 325 mesh equivalent to 44 μm. The required amount of titanate in a particular composition should be sufficient to result in a thin open or closed coating of 325 mesh titanate when all other components are removed. The compounds of the flux are all of micrometer size.
[0006] Although the fluxes disclosed in WO00 / 16940 provide improved penetration, the penetration is not optimal for steel substrates. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2000 / 16940 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, there is a need to improve the weld penetration of the steel substrate and thus the mechanical properties of the welded steel substrate. There is also a need to obtain an assembly of at least two metal substrates welded together by TIG welding, the assembly including a steel substrate. [Means for solving the problem]
[0009] To this end, the present invention comprises: Optionally, an anticorrosive coating; - a pre-coated steel substrate coated with a flux comprising at least one titanate and at least one nanoparticle selected from TiO2, SiO2, yttria stabilized zirconia (YSZ), Al2O3, MoO3, CrO3, CeO2 or mixtures thereof, wherein the thickness of the flux is between 30 and 95 μm.
[0010] The precoated steel substrate according to the present invention may also comprise any of the following features, taken individually or in combination: - Flux is Na 2 Ti 3 O 7 , K 2 TiO 3 , K 2 Ti 2 O 5 , MgTiO 3 , SrTiO 3 , BaTiO 3 , CaTiO 3 , FeTiO 3 and ZnTiO 4 or mixtures thereof; the flux further comprises an organic solvent; The proportion of nanoparticles is less than or equal to 80% by weight; The proportion of titanate is at least 45% by weight; the anticorrosive coating layer comprises a metal selected from the group consisting of zinc, aluminum, copper, silicon, iron, magnesium, titanium, nickel, chromium, manganese and alloys thereof; - at least one titanate has a diameter between 1 and 40 μm; The present invention may have any characteristic where
[0011] The present invention also relates to a method for producing a pre-coated steel substrate, the method comprising the following successive steps: A. providing a steel substrate; B. depositing a flux according to the present invention; C. Optionally, drying the coated metal substrate obtained in step B); Includes.
[0012] The method according to the invention may also comprise any of the following features, taken individually or in combination: the deposition of the flux is carried out by spin coating, spray coating, dip coating or brush coating; In step B), the flux contains 1 to 200 g / L of nanoparticles; - The flux contains 100~500g / L of titanate; The present invention may have any characteristic where
[0013] The present invention also relates to a method for manufacturing an assembly, said method comprising the following successive steps: I. Providing at least two metal substrates, at least one of the metal substrates being a pre-coated steel substrate according to the present invention; II. Welding at least two metal substrates by tungsten inert gas (TIG) welding; Includes.
[0014] The method according to the invention may also comprise any of the following features, taken individually or in combination: - TIG welding is carried out using a shielding gas that is an inert gas; -The current of the welding machine is between 10-200A; The present invention may have any characteristic where
[0015] The invention also relates to an assembly of at least two metal substrates at least partially welded together by tungsten inert gas (TIG) welding obtainable from the method according to the invention, said assembly comprising: at least one steel substrate, optionally coated with an anticorrosive coating; - at least one titanate and TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CEO 2 or a mixture thereof; and Includes.
[0016] The assembly according to the invention may also comprise any of the following features, considered individually or in combination: the second metal substrate is a steel substrate or an aluminum substrate; the second metal substrate is a pre-coated steel substrate according to the invention, The present invention may have any characteristic where
[0017] Finally, the invention relates to the use of the assembly obtainable from the method according to the invention for the manufacture of piping elements and parts of structures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The following terms are defined:
[0019] -Nanoparticles are particles between 1 and 100 nanometers (nm) in size.
[0020] -Titanates refer to inorganic compounds of the composition titanium oxide combined with at least one other oxide. They may be in the form of their salts.
[0021] - "Coated" means that the steel substrate is at least locally coated with flux. The coating can be limited, for example, to the area where the steel substrate is to be welded. "Coated" is inclusive of "directly" (without intermediate materials, elements or spaces disposed therebetween) and "indirectly" (with intermediate materials, elements or spaces disposed therebetween). For example, coating a steel substrate can include applying flux directly to a substrate with no intermediate materials / elements therebetween, as well as applying flux indirectly to a substrate with one or more intermediate materials / elements therebetween (such as an anti-corrosion coating).
[0022] Without being bound by any theory, it is believed that the flux primarily modifies the physical properties of the weld pool in the steel substrate, allowing for deeper fusion penetration. In contrast to patent application WO00 / 16940, in which titanate compounds are the essential components for improving weld penetration, in the present invention, it appears that not only the nature of the particles but also the size of the particles below 100 nm improves the penetration due to the improvement of the keyhole effect, the inverse Marangoni effect, the arc constriction and the arc stability caused by the depression in the surface of the weld pool.
[0023] In fact, titanates mixed with certain nanoparticles enable a keyhole mode, resulting in higher current densities and increased weld penetration, due to the combined effects of reverse Marangoni flow and constriction of the arc by electrical insulation. The keyhole effect refers to a literal hole, a depression in the surface of the weld pool, allowing the energy beam to penetrate even deeper. Energy is delivered to the joint very efficiently, which maximizes the weld depth and increases the weld depth-to-width ratio, thereby limiting distortion of the parts.
[0024] Additionally, the flux reverses Marangoni flow, which is mass transfer at a liquid-gas interface due to surface tension gradients. In particular, the flux components change the surface tension gradient along the interface. This change in surface tension results in a reversal of fluid flow toward the center of the weld pool, in this case resulting in improved weld penetration and wettability. Without wishing to be bound by any theory, it is believed that nanoparticles dissolve at a lower temperature than microparticles, thus allowing more oxygen to dissolve in the weld pool and activating the reverse Marangoni flow.
[0025] Additionally, nanoparticles have been observed to improve the uniformity of the applied flux by filling the gaps between the microparticles, which helps to stabilize the welding arc, thus improving weld penetration and quality.
[0026] Preferably, the nanoparticles are SiO 2 and TiO 2 and more preferably SiO 2 and TiO 2 Without being bound by any theory, it is believed that SiO 2 is mainly useful for increasing the penetration depth and removing and peeling off the slag, while TiO 2 It is believed that Ti mainly serves to increase the penetration depth and alloy with the steel, forming Ti-based inclusions that improve the mechanical properties.
[0027] Preferably, the nanoparticles have a size comprised between 5 and 60 nm.
[0028] Preferably, the proportion of nanoparticles in dry weight is less than 80%, preferably between 2 and 40%. In some cases, the proportion of nanoparticles may have to be limited to avoid too high fireproofing effect. A person skilled in the art who knows the fireproofing effect of each type of nanoparticle will adapt the proportion to each case.
[0029] The nanoparticles are selected from among sulfides or halides which are detrimental to carbon steel.
[0030] Preferably, the titanate has a particle size distribution between 1 and 40 μm, more preferably between 1 and 20 μm, advantageously between 1 and 10 μm. Indeed, without being bound by any theory, it is believed that this titanate diameter further improves the depression of the surface of the molten pool, the arc constriction and the inverse Marangoni effect.
[0031] Preferably, the flux is Na 2 Ti 3 O 7 , NaTiO 3 , K 2 TiO 3 , K 2 Ti 2 O 5 , MgTiO 3 , SrTiO 3 , BaTiO 3 , CaTiO 3 , FeTiO 3 and ZnTiO 4 or mixtures thereof. More preferably, the titanate is MgTiO 3 Indeed, without wishing to be bound by any theory, it is believed that these titanates further increase the penetration depth based on the effect of reverse Marangoni flow.
[0032] Preferably, the proportion by dry weight of the at least one titanate is greater than or equal to 45%, for example 50 or 70%.
[0033] According to one variant of the invention, the flux is applied onto a steel substrate and dried to form a coating, which is then composed of at least one titanate and TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CEO 2 or a mixture thereof.
[0034] According to another variant of the invention, the coating further comprises at least one binder that embeds the titanates and the nanoparticles and improves the adhesion of the flux on the steel substrate. Preferably, the binder is purely inorganic, in order to avoid the fumes that organic binders may generate, in particular during welding. Examples of inorganic binders are organofunctional silanes or siloxane sol-gels. Examples of organofunctional silanes are silanes functionalized in particular with groups from the groups amine, diamine, alkyl, amino-alkyl, aryl, epoxy, methacryl, fluoroalkyl, alkoxy, vinyl, mercapto and aryl. Amino-alkyl silanes are particularly preferred, since they greatly promote adhesion and have a long shelf life. Preferably, the binder is added in an amount of 1 to 20% by weight of the dry flux.
[0035] Preferably, the steel substrate is carbon steel.
[0036] Preferably, the anticorrosive coating comprises a metal selected from the group consisting of zinc, aluminum, copper, silicon, iron, magnesium, titanium, nickel, chromium, manganese and alloys thereof.
[0037] In a preferred embodiment, the anticorrosive coating is an aluminum-based coating comprising less than 15% Si, less than 5.0% Fe, optionally 0.1-8.0% Mg and optionally 0.1-30.0% Zn, balance Al. In another preferred embodiment, the anticorrosive coating is a zinc-based coating comprising 0.01-8.0% Al, optionally 0.2-8.0% Mg, balance Zn.
[0038] The anticorrosive coating is preferably applied to at least one side of the steel substrate.
[0039] The present invention also relates to a method for producing a precoated metal substrate, the method comprising the following successive steps: A. Providing a steel substrate according to the present invention; B. depositing a flux according to the present invention; C. Optionally, drying the coated metal substrate obtained in step B); Includes.
[0040] Preferably, in step A), the steel substrate is a carbon steel.
[0041] Preferably, in step B), the deposition of the flux is carried out by spin coating, spray coating, dip coating or brush coating.
[0042] Preferably, in step B), the flux is deposited only locally. In particular, the flux is applied to the area where the steel substrates are to be welded. It may be at the edge of the steel substrates to be welded or on a part of one side of the substrates to be welded. More preferably, the width of the applied flux is at least as large as the weld to be made, so that the arc constriction is further improved.
[0043] Advantageously, the flux further comprises an organic solvent. Indeed, without being bound by any theory, it is believed that the organic solvent allows for a well-dispersed coating. Preferably, the organic solvent is volatile at ambient temperature. For example, the organic solvent is selected from among volatile organic solvents such as acetone, methanol, isopropanol, ethanol, ethyl acetate, diethyl ether, non-volatile organic solvents such as ethylene glycol and water.
[0044] Preferably, the flux is 100-500g.L -1 of titanate, more preferably 175-250 g.L -1 Preferably, the flux contains between 1 and 200 g.L -1 of nanoparticles, more preferably 5-80 g.L -1 The nanoparticles include those between .
[0045] According to one variant of the invention, the flux of step B) is a mixture of at least one titanate and TiO 2 , SiO 2, yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CEO 2 or a mixture thereof, and at least one organic solvent.
[0046] According to another variant of the invention, the flux of step B) further comprises a binder precursor for embedding the titanates and the nanoparticles and improving the adhesion of the flux on the steel substrate. Preferably, the binder precursor is a sol of at least one organofunctional silane. Examples of organofunctional silanes are silanes functionalized in particular with groups from the group amine, diamine, alkyl, amino-alkyl, aryl, epoxy, methacryl, fluoroalkyl, alkoxy, vinyl, mercapto and aryl. Preferably, the binder precursor is present in an amount of 40 to 400 g.L of the flux. -1 is added in an amount of
[0047] If a drying step C) is performed, the drying is carried out by blowing air or an inert gas at ambient or elevated temperature. If the flux comprises a binder, the drying step C) is preferably also a curing step during which the binder is cured. Curing can be carried out by infrared (IR), near infrared (NIR) or in a conventional oven.
[0048] Preferably, the drying step C) is not carried out if the organic solvent is volatile at ambient temperature: indeed, after deposition of the coating, the organic solvent is expected to evaporate, resulting in a dry flux on the metal substrate.
[0049] The present invention also relates to a method for manufacturing an assembly, said method comprising the following successive steps: I. Providing at least two metal substrates, at least one of the metal substrates being a pre-coated steel substrate according to the present invention; II. Welding at least two metal substrates by tungsten inert gas (TIG) welding; Includes.
[0050] Preferably, in step II), the welding is carried out with a shielding gas which is an inert gas, for example selected from helium, neon, argon, krypton, xenon or mixtures thereof. Advantageously, the inert gas comprises at least argon.
[0051] Preferably, in step II), the current during welding is between 10 and 300 A. The welding can be performed with or without a filler material.
[0052] With the method according to the invention it is possible to obtain an assembly of at least a first metal substrate in the form of a steel substrate, optionally coated with an anticorrosive coating, and a second metal substrate, the first and second metal substrates being at least partially welded to one another by tungsten inert gas (TIG) welding, the weld zone being made of at least one titanate and a TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CEO 2 or a mixture thereof.
[0053] By "dissolved and / or precipitated flux" we mean that components of the flux can be drawn toward the center of the liquid-gas interface of the weld pool due to the reverse Marangoni flow and can be drawn further into the molten metal. Some components dissolve in the weld pool, resulting in an enrichment of the corresponding element in the weld. Other components precipitate and are part of a complex oxide that forms inclusions in the weld.
[0054] In particular, when the Al content of the steel substrate is greater than 50 ppm, the weld zone contains inclusions, including in particular Al-Ti oxides or Si-Al-Ti oxides or other oxides, depending on the nature of the nanoparticles added. These mixed element inclusions are smaller than 5 μm. Therefore, they do not impair the toughness of the weld zone. The inclusions can be observed by electron probe microanalysis (EPMA). Without being bound by any theory, it is believed that the nanoparticles promote the formation of inclusions of limited size, so that the toughness of the weld zone is not impaired.
[0055] Preferably, the second metal substrate is a steel substrate or an aluminium substrate. More preferably, the second steel substrate is a pre-coated steel substrate according to the invention.
[0056] Finally, the invention relates to the use of a coated metal substrate according to the invention for the production of piping elements and parts of structures. EXAMPLES
[0057] The following examples and tests should be considered as non-limiting in nature and for illustrative purposes only: they demonstrate advantageous features of the invention, the importance of parameters selected by the inventors after extensive experimentation, and further establish the properties achievable by the present invention.
[0058] For the test articles, steel substrates were used having the chemical compositions in weight percent disclosed in Table 1.
[0059] [Table 1] TIFF0007603610000002.tif15162
[0060] [Example 1] For test samples 1 to 3, MgTiO 3 (diameter: 2μm), SiO 2 (diameter range: 12-23 nm) and TiO 2An acetone solution containing MgTiO (diameter range: 36-55 nm) was prepared by mixing acetone with the elements. 3 The concentration is 175g.L -1 It was. SiO 2 The concentration is 25g.L -1 It was TiO 2 The concentration is 50g.L -1 Then, specimens 1 to 3 were coated with different thicknesses of acetone solution by spraying on an area larger than the weld to be made. The acetone was allowed to evaporate. The MgTiO in the coating 3 The proportion of SiO 2 The proportion of TiO 2 The proportion of was 20% by weight.
[0061] Test sample 4 was MgTiO 3 (diameter: 2μm), SiO 2 (diameter: 2 μm) and TiO 2 The membrane was coated with an acetone solution containing microparticles (diameter: 2 μm).
[0062] Test piece 5 was uncoated.
[0063] TIG welding was then applied to each specimen, with the welding parameters shown in Table 2 below.
[0064] [Table 2]
[0065] After TIG welding, the appearance of the coating on the welded area side was analyzed by naked eye and by field emission gun-scanning electron microscopy (FEG-SEM). Thermal images of the welding arc on the coating were taken. The composition of the welded area was analyzed by scanning electron microscopy (SEM). The specimens were bent to 180° according to standard ISO 15614-7. The hardness of both specimens was determined in the center of the welded area using a microhardness tester. The composition of the welded area was analyzed by energy dispersive X-ray spectroscopy and inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 3 below.
[0066] [Table 3]
[0067] The results show that Test Piece 2 improves TIG welding compared to the Control Test Piece.
[0068] Thermal images also confirmed that the combination of titanates and certain nanoparticles increased the heat flux, resulting in higher temperatures in the weld pool and higher gas pressures. Higher temperatures in the weld pool result in more heat transfer towards the lower regions of the weld pool due to reverse Marangoni convection, leading to increased melting and penetration of the base material.
[0069] [Example 2] Various coatings were tested by finite element method (FEM) simulations on a steel substrate. In the simulations, the flux was optionally MgTiO 3 (diameter: 2 μm) and nanoparticles with diameters of 10 to 50 nm. The coating thickness was 40 μm. Arc welding was simulated with each flux. The results of the simulated arc welding are shown in Table 4 below.
[0070] [Table 5]
[0071] The results show that the specimens according to the invention improve TIG welding compared to the comparative specimens.
[0072] [Example 3] For test item 19, an aqueous solution containing the following components was prepared: 363 g.L -1 MgTiO 3 (Diameter: 2μm), 77.8gL -1 SiO 2 (Diameter range: 12-23 nm), 77.8 g L -1 TiO 2 (diameter range: 36-55 nm) and 238 g.L -1 of 3-aminopropyltriethoxysilane (Dynasylan® AMEO from Evonik®). The solution was applied to a steel substrate and dried by 1) IR and 2) NIR. The dried coating was 40 μm thick and contained 62 wt. % MgTiO 3 , 13 wt.% SiO 2 , 13 wt.% TiO 2 and 12 wt. % of a binder derived from 3-aminopropyltriethoxysilane.
[0073] For test item 20, an aqueous solution containing the following components was prepared: 330 g.L -1 MgTiO 3 (Diameter: 2μm), 70.8gL -1 SiO 2 (Diameter range: 12-23 nm), 70.8 g L -1 TiO 2 (Diameter range: 36-55 nm), 216 g.L -1 of 3-aminopropyltriethoxysilane (Dynasylan® AMEO from Evonik®) and 104.5 gL -1 Functionalized nanoscale SiO with organofunctional silanes 2 The solution was applied to a steel substrate and dried by 1) IR and 2) NIR. The dried coating was 40 μm thick and contained 59.5% by weight of MgTiO 3 , 13.46 wt.% SiO 2, 12.8 wt% TiO 2 and 14.24 wt. % of a binder derived from 3-aminopropyltriethoxysilane and an organofunctional silane.
[0074] In all cases, the adhesion of the flux to the steel substrate was significantly improved.
Claims
1. 1. A pre-coated steel substrate, comprising: - optionally an anticorrosive coating; at least one titanate and TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CeO 2 or mixtures thereof, the thickness of the flux being between 30 and 95 μm, the at least one titanate having a dry weight percentage of 45-70% based on the total weight of the flux and a particle size distribution of between 1 and 40 μm, and the at least one nanoparticle having a dry weight percentage of 15-80% based on the total weight of the flux and a diameter range of the nanoparticles being between 1 and 100 nm; Coated with, pre-coated steel substrate.
2. The precoated steel substrate of claim 1 , wherein the flux further comprises a binder.
3. 3. The precoated steel substrate of claim 2, wherein the dry weight percentage of the binder in the flux is between 1 and 20% based on the total weight of the flux.
4. 4. The precoated steel substrate of any one of claims 1 to 3, wherein the anticorrosive coating comprises a metal selected from the group consisting of zinc, aluminum, copper, silicon, iron, magnesium, titanium, nickel, chromium, manganese and alloys thereof.
5. A method for manufacturing a precoated steel substrate according to any one of claims 1 to 4, comprising the following successive steps: A. Providing a steel substrate, optionally coated with an anticorrosive coating; B. At least one titanate and TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CeO 2 or mixtures thereof, wherein the at least one titanate has a dry weight percentage of 45-70% relative to the total weight of the flux and has a particle size distribution between 1-40 μm, and the at least one nanoparticle has a dry weight percentage of 15-80% relative to the total weight of the flux and has a diameter range between 1-100 nm; C. Optionally, drying the coated steel substrate obtained in step B); A method comprising:
6. 6. The method according to claim 5, wherein in step B) the deposition of the flux is carried out by spin coating, spray coating, dip coating or brush coating.
7. 7. The method according to claim 5, wherein in step B) the flux further comprises an organic solvent.
8. The method according to claim 7, wherein in step B) the flux comprises 1-200 g / L of nanoparticles.
9. 9. The method according to claim 7 or 8, wherein in step B) the flux comprises 100-500 g / L of at least one titanate.
10. The method according to any one of claims 5 to 9, wherein in step B) the flux further comprises a binder precursor.
11. A method for manufacturing an assembly comprising the following successive steps: I. Providing at least two metal substrates, at least one of the metal substrates being formed of at least one titanate and TiO 2 , SiO 2 , yttria stabilized zirconia (YSZ), Al 2 O 3 , MoO 3 , CrO 3 , CeO 2 or a mixture thereof, wherein the thickness of the flux is between 30-95 μm, the at least one titanate has a dry weight percentage of 45-70% based on the total weight of the flux and a particle size distribution of 1-40 μm, and the at least one nanoparticle has a dry weight percentage of 15-80% based on the total weight of the flux and a diameter range of between 1-100 nm; II. Welding at least two metal substrates by tungsten inert gas (TIG) welding; A method comprising:
12. 12. The method according to claim 11, wherein in step II) TIG welding is performed with a shielding gas which is an inert gas.
13. The method according to any one of claims 11 or 12, wherein in step II) the current of the welding machine is between 10 and 300 A.
Citation Information
Patent Citations
Argon tungsten-arc welding soldering flux and method adopting same for welding
CN102862004A
Flux for deep penetration arc welding and welding method using the same
JP2002120088A
Active flux for tungsten inert gas arc welding for steel
JP2010005696A
Welding Flux for Stainless Steel
US20100288397A1
Silver-containing Antiseptic Welding Flux for Stainless Steel
US20120234814A1
